Leader Humor And Knowledge Sharing Behavior: The Role Of Leader-Member Exchange - Muhammad Rasyid Abdillah (Jurnal Manajemen, 2022)
A function of using humour in the workplace is to build relationships between employees involved in such behaviour. This study seeks to explain the relationship between leader humour and knowledge-sharing behaviour using social exchange theory. Specifically, this study endeavours to explain the mechanism process underlying the relationship between leader humour and knowledge-sharing behaviour through the leader-member exchange. To test the hypotheses, the current study collected data from employees working at communication and information companies in Pekanbaru City, Riau, Indonesia utilizing PLS-SEM analysis. The finding shows that leader humour can encourage employee knowledge sharing behaviour through the relationship quality between leaders and employees.